Liver insulinization as a driver of triglyceride dysmetabolism - Cook, Joshua R; Hawkins, Meredith A; Pajvani, Utpal B (Nature metabolism, 2023)
Metabolic dysfunction-associated fatty liver disease (MAFLD) is an increasingly prevalent fellow traveller with the insulin resistance that underlies type 2 diabetes mellitus. However, the mechanistic connection between MAFLD and impaired insulin action remains unclear. In this Perspective, we review data from humans to elucidate insulin's aetiological role in MAFLD. We focus particularly on the relative preservation of insulin's stimulation of triglyceride (TG) biosynthesis despite its waning ability to curb hepatic glucose production (HGP). To explain this apparent 'selective insulin resistance', we propose that hepatocellular processes that lead to TG accumulation require less insulin signal transduction, or 'insulinization,' than do those that regulate HGP. As such, mounting hyperinsulinaemia that barely compensates for aberrant HGP in insulin-resistant states more than suffices to maintain hepatic TG biosynthesis. Thus, even modestly elevated or context-inappropriate insulin levels, when sustained day and night within a heavily pro-lipogenic metabolic milieu, may translate into substantial cumulative TG biosynthesis in the insulin-resistant state.